The development of modern logic - Haaparanta, Leila, 1954- (New York ; Oxford : Oxford University Press, 2009)
This volume presents a comprehensive history of modern logic from the Middle Ages through the end of the 20th century. In addition to a history of symbolic logic, the contributors also examine developments in the philosophy of logic and philosophical logic in modern times.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Logic -- History